(untitled) (Malaysian Journal of Civil Engineering, 2018)
A construction delay is anything that impedes the ability of a certain obliged party to maintain a schedule. Delays manifest during all project phases, where they might initiate even in the design phase. There exist a limited volume of studies in the literature that have analysed delay problems or the outcomes on strategies for mitigating the delays in the planning and design phases, specifically for the Public Works Department (PWD) construction projects. Hence, this research aims to assess the extent of delay issues in PWD construction projects, their critical causes, and the possible strategies or opportunities to minimize delays in the planning and design phases. Information from SKALA JKR was retrieved to enable analysis of delay issues in PWD construction projects to be carried out. Meanwhile, a structured questionnaire was also disseminated to two main target groups which were, PWD officers and private consultants. Mean index and relative importance index (RII) analysis methods were adopted to rank delay causes in terms of their severity as perceived by the respondents. Delays in the planning and design phases for PWD construction projects were literally in a critical state. Changes in clients’ requirements, poor scope definition and miscommunication were among the most critical causes of delay in the planning and design phases. The communication aspect could have been the principal key strategy to resolve some major delay causes, in the effort to mitigate delays in the planning and design phases, as well as in the construction phase